PENGARUH KEPUASAN KERJA DAN STRES KERJA TERHADAP KINERJA PERSONIL PLETON I YONKAV 6/NK KODAM I BUKIT BARISAN - Sri Gustina Pane (Jurnal Prodi Fakultas Ekonomi-UISU, 2019)
The term of this study is: Does the job satisfaction, and work stress affect on employee performance at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN.The aim of the study is to determine the effect of job satisfaction, and work stress of employees performance at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN.The sample of this study were 50 employees at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN. The technique of the data analysis in this research is Multiple Linier Regression Analysis.The results of this study show that job satisfaction has a positive and significant influence on Employee Performance and work stress has a negative and significant influence on Employee Performance at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN, finally job satisfaction, and work stress simultaneously have a significant effect on Employee Performance at Pleton I YONKAV 6/NK KODAM I BUKIT BARISAN.Keywords : Job Satisfaction, Work Stress and Employee Performance